Robustness in econometrics - Kreinovich, Vladik; Songsak Sriboonchitta; Huynh, Van-Nam (Springer, 2017)
This book presents recent research on robustness in econometrics. Robust data processing techniques? i.e., techniques that yield results minimally affected by outliers? and their applications to real-life economic and financial situations are the main focus of this book. The book also discusses applications of more traditional statistical techniques to econometric problems. Econometrics is a branch of economics that uses mathematical (especially statistical) methods to analyze economic systems, to forecast economic and financial dynamics, and to develop strategies for achieving desirable economic performance. In day-by-day data, we often encounter outliers that do not reflect the long-term economic trends, e.g., unexpected and abrupt fluctuations. As such, it is important to develop robust data processing techniques that can accommodate these fluctuations.
Keywords: Econometrics.; elektronické knihy; electronic books